Creative Thinking Development through Project-based Learning of Pre-service Teachers in Teaching Islamic Studies - Binbai, Sumai (Electronic Journal of Open and Distance Innovative Learning (e-JODIL), 2024)
The development of the professional capabilities of pre-service teachers to adapt to various changes is a critical task for teacher education institutions. Key skills for teachers in the 21st century, which will lead them towards effective learning innovation, include fostering creativity and project-based skills. This research aims to develop pre-service teachers by 1) investigating the creativity skills of pre-service teachers in Islamic education before and after implementing project-based learning, 2) assessing the creative media project skills of pre-service teachers after implementing project-based learning, 3) evaluating the outcomes of creative media projects produced by pre-service teachers. The study is the classroom action research conducted with students enrolled in course 762-318, "Multimedia Production for Learning," totaling 30 participants. Research tools include 1) four project-based learning management plans 2) a creativity skills assessment 3) project skills assessment 4) creative media project outcomes assessment. The researchers collected data before and after the implementation of project-based learning and analyzed it using mean, standard deviation, and t-test. The findings are as follow: 1. Creative thinking skills of pre-service teachers after learning with project-based learning are significantly higher than before learning at the level of 0.05. When considering specific skills from the drawing and completing images test, students showed the highest level of detail-oriented creative thinking skills, with a mean score of 4.00. For the second test, involving drawing pictures and writing short stories to accompany them, students exhibited the highest level of flexible thinking skills, with a mean score of 4.03. 2. Project-based learning enhances all aspects of innovation project management skills of pre-service teachers at a high level; the highest mean score is media product ( =4.06, S.D. = 0.37), management process ( =3.87, S.D. = 0.36), and report writing ( =3.87, S.D. = 0.36) respectively. 3. Pre-service teachers were able to produce creative media at a high level, with creative thinking skills ranging from 3.50 to 3.81 across all dimensions.